EL MITO DE HERCULES Y ALFONSO X EL SABIO EN DOS ESCRITORES BARROCOS: SAAVEDRA FAJARDO Y JUAN DE MARIANA - de Gea, B. Rosa (Res Publica. Revista de Historia de las Ideas Políticas, 2023)
The author analyses the different treatment of the figure of the myth of Hercules in two historic works from the Spanish baroque: Corona Gótica by the diplomat Saavedra Fajardo and De rebus hispaniae by the Jesuit Juan de Mariana. The significance of the mythical hero is traced in medieval Spanish historiography and its later derivations, which are revealed as discourses legitimising different postures in the face of the imperial idea.
Keywords: Myth; history; empire